Organización Contable en PINZON CHAMBA AUNER EDUARDO, de la ciudad de Loja, período Abril - Mayo del 2022. - Coronel Ordoñez, Jazmin Alexandra (2022)
The Curriculum Integration Work entitled Accounting Organization in “PINZON CHAMBA AUNER EDUARDO”, from the city of Loja, period April - May 2022, was developed with the finality of knowing the economic-financial situation of the company through the accounting organization which will allow the optimization of management in the economic-administrative field. The objectives of the Curricular Integration Project were developed through the execution of the accounting process for which a plan and manual of accounts were designed in agreement with the needs of the company, which facilitates the registration of the economic activities which are carried out by the same; the inventories were carried out through the physical verification of goods, values, rights, and obligations based in the documentation source, with this information the Initial Situation Statement was prepared, purchase assistants, sales, accounts payable and receivable, Daily Book, Book Ledger, Trial Balance, Work Sheet, FInancial Statements and Cash Flow Statements. Concluding the investigative work, it is determined that the accounting organization is of vital importance, the accounting processes and techniques allow for collecting clear and orderly information of its activities, helping to organize and control the resources, in order to achieve better economic benefits which are manifested in the positive results of the exercise with the net profit of the year of $6.995,43; assets of $109.451,43; liabilities of $4.812,77 and equity of $104.638,66 information that is important to its owner for decision-making based on the economic growth of the business.